The effect of NPK treatments on the Cu and Fe content of winter wheat (Triticum aestivum L.) - Burján, Zita; Móré, Mariann; Czakóné Vágó, Xénia; Győri, Zoltán (Acta Agraria Debreceniensis, 2013)
In this study the effect of N, P and K nutrients on the Cu and Fe content of winter wheat (Triticum aestivum L.) grains was investigated in a long-term fertilization experiment set up in Nagyhörcsök. Samples were also harvested from four experimental stations of the Hungarian national long-term fertilization trials. These are the following: Bicsérd, Iregszemcse, Karcag, and Putnok. Plant samples were collected in 2005 which was very wet. Our results from Nagyhörcsök were compared with the Cu and Fe content of samples which were harvested from control plots of other experimental stations. The Cu and Fe content of grain samples were measured using inductively coupled plasma mass spectrometer (ICP-MS) followed by digestion with HNO3-H2O2 solution. All data were subjected to ANOVA, and when significant differences (P<0.05) were detected, Duncan’s test was performed to allow separation of means. The main conclusions are as follows: Cu and Fe content of wheat grains was higher and higher in every NPK treatments. Samples were harvested from the control plots of Iregszemcse and Bicsérd have higher Cu content than the treated samples from Nagyhörcsök.